Resting cortisol concentrations in dogs presenting to a university teaching hospital with collapse - Ana Fernandez Gallego; Craig Robert Breheny; Adam G. Gow; Alisdair M. Boag (Journal of Veterinary Internal Medicine, 2024)
Abstract Background The relationship between collapse and a diagnosis of hypoadrenocorticism is not well understood in dogs. Hypothesis To assess the prevalence of episodes of collapse in dogs screened for hypoadrenocorticism, and to assess the prevalence of confirmed hypoadrenocorticism in dogs presenting with reported collapse. Animals Seventy‐three client‐owned dogs with resting cortisol concentrations were measured and presented to a University teaching hospital for collapse. Methods Retrospective review of medical records of dogs at a single center. Results The prevalence of episodes of collapse in dogs that had a resting cortisol measurement was 73/856 (8.5%; 95% confidence interval [95% CI], 6.7%‐10.6%). Resting cortisol concentration was <2 μg/dL (<55 nmol/L) in 19 dogs. Cortisol concentration after ACTH stimulation was <2 μg/dL (<55 nmol/L) in 1 of the 73 dogs in this cohort, consistent with a diagnosis of hypoadrenocorticism, giving a prevalence estimate of hypoadrenocorticism of 1.3% (95% CI, 0.15%‐6.2%). In 8 dogs with an initial resting cortisol concentration <2 μg/dL (<55 nmol/L), hypoadrenocorticism was excluded based on a repeat resting cortisol concentration >2 μg/dL (>55 nmol/L). The most common diagnosis was vasovagal syncope (10/73), followed by sick sinus syndrome and third‐degree atrioventricular block (2/73). The final diagnosis was unknown in 24/73 dogs. Conclusions and Clinical Importance Hypoadrenocorticism was the final diagnosis in 1 of 73 dogs presented to a teaching hospital either in a collapsed state or with a previous history of episodes of collapse. No dog presenting as cardiovascularly stable for intermittent collapse was found to have hypoadrenocorticism.